Estrategias de aprendizaje utilizadas por estudiantes de primaria en proceso de alfabetización - Mello, Fabiane de Oliveira (2022)
The general objective of this research was to verify and analyze qualitatively the repertoire of learning strategies used by students with and without learning difficulties under literacy process. Eight 8-year-old students participated in the research, being four from the Regular Education Classroom and four from the Resource Room. It was applied, individually, a semi-structured interview. The results evidenced higher frequency in the use of cognitive strategies and differences between both students’ groups regarding the use of cognitive and resource administration strategies. The dysfunctional strategies showed themselves with higher frequency by the students from the Resource Room. It is suggested that the teachers improve their knowledge on learning strategies, in order to enable their students a more meaningful and autonomous learning.